Socio Demographic Profile and Risk Factors Of Women Presenting With Cervical Cancer in A Tertiary Care Center in Bangladesh - Shirin, Fahmida; Ferdous, Jannatul; Karim, Tanjila; Islam, Fahmida; Khanam, Zubaida (Journal of Chittagong Medical College Teachers’ Association, 2017)
Background : Bangladesh, a densely populated country of South-East Asia shows some of the highest rates of cervical cancer worldwide , and about 70% of the population is living in rural villages with a per capita GDP of 1211 US (Year 2015) having no population based cancer registry. The aim of this study was to assess the socio demographic status and risk factors related to cervical cancer in a tertiary care center in Bangladesh. Material and methods : A crosssectional study was conducted using a self administered questionnaire between January 1,2016 and June 30, 2016 on 68 patients who were admitted in Chittagong Medical College Hospital for confirmation of diagnosis and treatment. Results : Women of increasing age 40-50 (41.18%), having many pregnancies >4 ( 38.23%) and no education 63 (92.65%)with history of active or passive smoking 56 (82.36%) were found to be at increased risk of cervical cancer. Conclusion : It is important to recognize the socio demographic and risk factors associated with cervical cancer while making public health policies and implementation of cervical cancer control programmes. JCMCTA 2017 ; 28 (1) : 63 - 66